2019
DOI: 10.1111/nph.16281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phytic acid mutants in oilseed rape (Brassica napus) by large‐scale screening of mutant populations through amplicon sequencing

Abstract: Brassica napus (oilseed rape) is an important oil crop in temperate regions, which originated from hybridization of Brassica oleracea and Brassica rapa. Owing to its polyploidy, the functional study of single genes is cumbersome. Phytic acid is considered as an antinutritive compound, and we aimed to knock out the underlying synthesis and transporter genes to identify low phytic acid mutants.We implemented a high-throughput next-generation sequencing screening protocol for an ethylmethane sulfonate population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…The rcm1 mutant was obtained from an EMS-mutagenized population. EMS mutagenesis is widely used in the construction of mutant libraries and in plant functional genomics 37 , 38 . For instance, the hst1 mutant generated from EMS mutagenesis was crossed with the wild type to map the OsRR22 gene 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The rcm1 mutant was obtained from an EMS-mutagenized population. EMS mutagenesis is widely used in the construction of mutant libraries and in plant functional genomics 37 , 38 . For instance, the hst1 mutant generated from EMS mutagenesis was crossed with the wild type to map the OsRR22 gene 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the super family of ATP‐grasp fold proteins and is involved in photomorphogenesis by interacting via the COP9 signalosome, in stress responses, in signal transduction and in seed coat development (Du et al , 2011; Qin et al , 2005; Sweetman et al , 2007; Tang et al , 2013). In our previous study, we have identified EMS (ethyl methanesulphonate)‐induced loss‐of‐function mutations in six genes of the PA biosynthesis pathway (Sashidhar et al , 2019). However, due to gene redundancy in polyploid rapeseed noticeable phenotypic effects could only be observed in plants carrying multiple mutations which required time‐consuming crossing experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study had shown determining the level of transcription of candidate genes in the seed at different time points after flowering helped to identify candidate genes. 13 , 14 In this study, the genes related to phytate concentration and content within the LD decay region (∼300 kb) of each significant SNP in B. napus were screened. The transcriptional profile of these genes was employed to help narrow down the list of candidate genes, and finally 30 candidates were identified.…”
Section: Discussionmentioning
confidence: 99%